THE EFFECT OF SELF-CONCEPT AND SELF-CONFIDENCE ON STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITIES - Indah Aini Wirdia; Asrul Asrul (Prima: Jurnal Pendidikan Matematika, 2026)
This study aims to determine the influence of self-concept and self-confidence on students’ mathematical creative thinking ability at MTs Negeri Serdang Bedagai. This quantitative research used a correlational design with a sample of 32 students selected through cluster sampling. Data were collected using questionnaires for self-concept and self-confidence, and a test for creative mathematical thinking skills. The data were analyzed using multiple regression with SPSS 23. The results showed that self-concept had a positive and significant effect on creative mathematical thinking (Sig. = 0.016 < 0.05), self-confidence also had a positive and significant effect (Sig. = 0.003 < 0.05), and simultaneously both variables significantly influenced students’ creative mathematical thinking ability (Sig. = 0.010 < 0.05) with a determination coefficient (R²) of 0.289. These findings indicate that self-concept and self-confidence play an important role in improving students’ mathematical creative thinking ability.